2017
DOI: 10.4172/2157-7099.1000471
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Epiretinal Membrane Bridging, Visual Acuity and Central Macular Thickness

Abstract: Epiretinal membrane or macular pucker is avascular, fibrocellular membrane that develops on the inner surface of the retina that can result in various stages of macular dysfunction. Fine epiretinal membranes lead to minimal visual loss, whilst epiretinal membranes (that may or may not bridge the fovea) are, in their more severe stages, accompanied by macular edema and image distortion that is caused by pronounced tractional membranes and perifoveal capillary leakage. Macular edema and its' type, as well as epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Pilli et al (20) demonstrated the relationship between the increase in central macular thickness and the deterioration of macular morphology and decreased visual acuity. In their histological study, Paovic et al (21) reported that visual acuity decreased in the central macular thickness increase due to ERM-related macular edema. Dawson et al (22) reported that visual acuity decreased with central macular thickness increase and visual acuity increased in patients with decreased central macular thickness following macular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Pilli et al (20) demonstrated the relationship between the increase in central macular thickness and the deterioration of macular morphology and decreased visual acuity. In their histological study, Paovic et al (21) reported that visual acuity decreased in the central macular thickness increase due to ERM-related macular edema. Dawson et al (22) reported that visual acuity decreased with central macular thickness increase and visual acuity increased in patients with decreased central macular thickness following macular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the early increase in RNFL thickness and the late ONL thinning might be explained by the traumatic action of surgical traction of the inner layers in the foveal region. Coherently with this theory, postoperative VA has been negatively correlated to ERM adherence, and foveal bridging is an indicator of bad functional outcome after surgery [ 25 , 26 ]. Differently from Song et al [ 16 ], we did not find a higher preoperative GCL/CMT ratio to be correlated with better visual prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis showed that in both groups (epiretinal membranes or without a epiretinal membrane bridging the fovea), there was no significant difference on the visual acuity. The authors observed that a relationship between epiretinal membrane that bridges the fovea and the central macular thickness occurred [3].…”
mentioning
confidence: 99%
“…Paovic et al [3] presents the research article entitled "Correlation between Epiretinal Membrane Bridging, Visual Acuity and Central Macular Thickness". The aim of the presented study was to determine to what extent the epiretinal membrane, that bridges or not bridges the fovea, exerts an influence on the visual acuity.…”
mentioning
confidence: 99%